2022
DOI: 10.3390/ijms23094985
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death by Entosis: Triggers, Molecular Mechanisms and Clinical Significance

Abstract: Entosis—a homotypic insertion of one cell into another, resulting in a death of the invading cell—has been described in many reports, but crucial aspects of its molecular mechanisms and clinical significance still remain controversial. While actomyosin contractility of the invading cell is very well established as a driving force in the initial phase, and autophagy induced in the outer cell is determined as the main mechanism of degradation of the inner cell, many details remain unresolved. The multitude of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…8 A and B). RHOA/ROCK-controlled pathways and actomyosin contractility of the invading cell are the known driving force for the initiation of entosis 45 , 46 , which is in agreement with our observation that entosis of HGSC cells is dependent on both MYPT1 and ROCK (Fig. 9 A and B).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…8 A and B). RHOA/ROCK-controlled pathways and actomyosin contractility of the invading cell are the known driving force for the initiation of entosis 45 , 46 , which is in agreement with our observation that entosis of HGSC cells is dependent on both MYPT1 and ROCK (Fig. 9 A and B).…”
Section: Discussionsupporting
confidence: 92%
“…9 A). Even though the association of entosis with progression of HGSC remains to be investigated, entosis may contribute to cancer cell survival under stress conditions (such as chemotherapy) 45 , 46 as well as to their escape from immune surveillance 132 . Furthermore, MYPT1 phosphorylation is induced by LPA in both OCMI91s and OVCAR8 cells with different LPAR expression profile ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2007, Overholtzer et al [ 7 ] reported that detached epithelial cells can also take an alternative route to death called entosis, which is driven by cell-in-cell invasion ( Figure 1 C). For this Special Issue, Kianfar et al [ 8 ] summarized the current knowledge of molecular mechanisms and clinical data on entosis, highlighting both conclusive explanations and controversies.…”
mentioning
confidence: 99%